Video : A Retrospective : Long Beach Museum of Art 1974-1984 - Hendrick, Barbara; Huffman, Kathy Rae; Ross, David A.; Viola, Bill; Perov, Kira; Yapelli, Tina; Long Beach City Council, Long Beach (Long Beach : Long Beach Museum of Art, 1984)
Paik, Nam June ; Fox, Terry ; Glassman, Joel ; Gillette, Frank ; Viola, Bill ; Smith, Alexis ; Downey, Juan ; Wegman, William ; Rosler, Martha ; Kurtz, Bruce ; Davis, Douglas ; Kubota, Shigeko ; etc.
Video : A Retrospective 1974-1984, published in conjunction with a two-part exhibition, Long Beach Museum of Art, Long Beach, September 9 - November 4, 1984 and November 25, 1984 - January 20, 1985
Engels
kunstcatalogus